A Structural Topic Model of the Features and the Cultural Origins of the Baconian Program - Peter Grajzl; Peter Murrell (Center for Economic Studies and ifo Institute (CESifo), 2017)
We use machine-learning methods to study the features and origins of the Baconian program, a cultural and methodological paradigm viewed as providing the intellectual roots for modern economic growth. After building a machine-readable corpus of Bacon's works, we estimate a structural topic model, a state-of-the-art technique for analysis of text corpora. The estimates uncover the dominant themes in Bacon's opus, clearly identifying two central to the Baconian program: the emphasis on probing for facts and the epistemology of deriving lessons from those facts. Examining the connectedness of the themes, clear evidence links Bacon's epistemology to his jurisprudence. The emphasis on seeking facts is linked to Bacon's epistemology but is less connected with other themes, and therefore much more sui generis with Bacon. The utilitarian promise of science, embraced by Bacon's followers, is not emphasized by Bacon. Finally, we demonstrate how Bacon's use of the different themes varies with the intended audience and his chosen medium.
Keywords: B31; Z10; C55; N73; K10; P10; 330; Baconian program; culture; law; knowledge; natural philosophy; politics; religion